The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.ijmedinf.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting end-user expectations to guide the implementation process of a new electronic health record: A case study using concept mapping

Abstract: Concept mapping is an effective method to find topics that, according to healthcare professionals, are important to consider during the implementation of a new EHR. The method helps to combine the input of a large group of stakeholders at limited efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…Anecdotal comments revealed that students enjoyed creating the maps, which facilitated their understanding of the complexity of the healthcare system and digital health technologies. These findings were also similar to those of other studies that utilized mind maps as a creative way to enhance learning (Abd El‐Hay et al, 2018: Carter‐Templeton et al, 2016: Joukes et al, 2016; Mammen & Mammen, 2018).…”
Section: Discussion and Nursing Implicationssupporting
confidence: 90%
See 1 more Smart Citation
“…Anecdotal comments revealed that students enjoyed creating the maps, which facilitated their understanding of the complexity of the healthcare system and digital health technologies. These findings were also similar to those of other studies that utilized mind maps as a creative way to enhance learning (Abd El‐Hay et al, 2018: Carter‐Templeton et al, 2016: Joukes et al, 2016; Mammen & Mammen, 2018).…”
Section: Discussion and Nursing Implicationssupporting
confidence: 90%
“…In the healthcare setting, concept maps and mind maps were useful in determining requirements for EHR implementation needs (Joukes, Cornet, de Bruijne, & De Keizer, 2016; Kabukye, de Keizer, & Cornet, 2020); visualizing themes for big data research (Gu, Li, Li, & Liang, 2017); evaluating mobile applications for consumer use (Lee & Kim, 2018); determining organizational actions related to providing patient‐centered care (Ogden, Barr, & Greenfield, 2017); creating a health equity toolkit (Pauly et al, 2018); and creating a method to visualize and manage digital data (Mammen & Mammen, 2018). Focus groups, interviews, surveys, and brainstorming were common methods used to solicit content for concept maps in all the studies.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…With the gradual shift from paper to electronic health records (EHRs), opportunities and challenges associated with presentation of healthcare data have emerged (Jensen and Bossen, 2016). Although previous studies report different outcomes about the impact of EHRs on the quality of healthcare (Buntin et al, 2011; Joukes et al, 2016; Mohan et al, 2013; Nguyen et al, 2014; Pollak and Lorch, 2007), improving the quality of documentation is often regarded as one of the advantages of EHRs (Nguyen et al, 2014). On the other hand, quality and accuracy of data is an important contributing factor for a better acceptance of EHRs (Häyrinen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Further research is therefore needed to explore factors related to the low clinical uptake of remote services in hearing healthcare and especially those related to HA support and management. A review of concept mapping (CM), a useful methodology in implementation science research (Joukes et al 2016), is provided below. CM is a participatory research method, with stakeholder involvement spanning the entire process.…”
Section: Introductionmentioning
confidence: 99%